Information to parents during childhood cancer treatment: a descriptive study - Fernanda Machado Silva-Rodrigues; Karoline dos Santos Rodrigues Moraes; Adriana Maria Duarte; Naiara Barros Polita; Marcele Pescuma Capeletti Padula; Lucila Castanheira Nascimento (Universidad de Alicante, 2019)
Objective: The study aimed to explore the perspective of parents of children with cancer when searching for information at different points in the treatment. Method: This is a descriptive study with qualitative data analysis. Semistructured interviews were conducted with 22 parents at two public hospitals in the city of São Paulo, Brazil. The data were analyzed using inductive content analysis. Results: We did not observe a pattern in the search for information during the disease trajectory, but different needs regarding the type of information as the child or adolescent advances within the therapeutic plan. The primary sources of information were: doctors, other health professionals than nurses and the internet. The doctor remains the reference as a source of information. Nurses presented a very modest role concerning their possibilities to serve as educators and information providers. Parents stressed the need for precise and individualized information. Conclusions: The professionals involved in the care for this population are expected to be ready to provide information and to adopt strategies to simplify the information given to enable these families for care and for the decision-making process during treatment.